Bed roughness effects on characteristics of turbulent confined wall jets. (July 2018) - Shojaeizadeh, Ali; Safaei, Mohammad Reza; Alrashed, Abdullah A.A.A.; Ghodsian, Masoud; Geza, Mengistu; Abbassi, Mohamed Ammar
Graphical abstract: Studied surface with average roughness of 1.05 mm. Highlights: Effects of bed roughness on turbulent wall jet flow were investigated experimentally. Time-averaged values of velocities were used to calculate the turbulence parameters. Increasing surface roughness, rate of growth length of longitudinal scale decreases. When distance increases from jet exit, bed shear stress decreases. Maximum value of turbulence intensity is reduced by surface roughness decrement. Abstract: In this paper, effects of bed roughness on the flow pattern and turbulence characteristics, such as velocity contours, shear stresses, Reynolds stresses and turbulence intensities on a three-dimensional wall jet were investigated experimentally. The experiments have been conducted in a channel which is made of metal floor and glass walls, width 0.57 m, height 1 m and length 10 m. Jet was settled using a pipe with internal diameter of 20 mm over a horizontal bed. A velocimeter was used to measure the flow velocity at three directions. The time-averaged values of velocities were used to calculate the turbulence characteristics. The results showed that with increasing surface roughness, the rate of growth length of longitudinal scale decreases, while decay rate and jet velocity increases. Moreover, the maximum value of turbulence intensity is augmented with increasing the surface roughness. When surface roughness increases, the rate of length scale decreases and decay of jet velocity enhances. Whereas u-component of turbulence intensity increases by surface roughness increment. Also, when distance increases from jet exit, bed shear stress decreases and when surface roughness increases, surface shear stress enhances. The vertical distribution of w ̂ for various x ̂ showed that the vertical direction of velocity has changed from descending to ascending in x/d = 45 to x/d = 55 due to the existence of backflow and consequently the creation of a vortex. Furthermore, with an increase in surface roughness, the decay of W component of velocity has increased.